An experimental study on premixed syngas/air flame propagating across an obstacle in closed duct. (1st May 2020) - Yang, Xufeng; Yu, Minggao; Zheng, Kai; Luan, Pengpeng; Han, Shixin
Highlights: Flame propagation across a fence-type obstacle in closed duct was experimentally studied. Tulip flame is observed after the flame propagates through the obstacle opening. Vortex motion is created by obstacles results in a new pattern of tulip flame development. Flame serves a more drastic shape change in the obstructed duct after inversion. The coupling effect of obstacles and hydrogen volume fractions on flame propagation is studied. Abstract: This paper studies the effect of obstacle on the propagation of the premixed flame. Experiments are conducted in a closed rectangular duct that house a pair of fence-type obstacles with various blockage ratios (BR = 0, 0.3, and 0.5) mounted both on top and bottom walls of the duct employing the stoichiometric syngas/air mixtures with various hydrogen volume fractions (0% ≤ x (H2 ) ≤ 50%). High-speed camera and piezoelectric pressure gauges are respectively employed to track the propagation of the premixed flame complex and overpressure dynamics. The presence of obstacles changes the flame front shape and breaks the flame surface. The flame will still invert and the tulip flame forms after propagation through the obstacle opening. There is a new pattern of tulip flame development because of the vortex motion caused by the obstacles. After inversion, obstacles and hydrogen volume fractions are coupled to affect the propagation dynamics. The flame maintains in tulip shape as x (H2 ) = 0%, but the flame oscillates and undergoes a more drastic shape change as x (H2 ) ≥ 10%. The characteristic time decreases, but the maximum flame tip speed increases, as hydrogen volume fraction increases significantly as 0% ≤ x (H2 ) < 10% and gradually as x (H2 ) ≥ 10%. The presence of the obstacles has no effect on the flame touching the duct walls, but accelerates the flame inversion and propagation to the discharge vent. The maximum flame tip speed increases with blockage ratios. Finally, the corresponding of flame tip speed and overpressure profile is specially observed and discussed.